Captain Awesome says the magic word - Kirby, Stan (Kirby, Stan. Captain Awesome, 2020)
"After seeing a real-live magic show, Eugene has decided he wants to become a magician. So he studies magic tricks and practices them on anyone he can: his best friends, his parents, and even his baby sister. Then his teacher announces that her students will all be sharing something new they've learned recently, and Eugene knows this is the perfect chance to show his skills. For his biggest trick yet, Eugene will make the class pet hamster, Turbo, disappear! But when Eugene says the magic word, Turbo actually does disappear. Did Eugene's magic really work?"--Amazon.com.